Essentials of Anatomic Pathology - Cheng, Liang; Bostwick, David G.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
In the 8 years since the publication of the first edition of Essentials of Anatomic Pathology, great strides have been made in our understanding of diseases and neoplastic processes. Many clinically important new histopathologic entities have been described or more fully defined in virtually every organ. Numerous clinically important diagnostic and prognostic markers have entered routine practice. Genetic testing for the early detection of cancers and the molecular classification of diseases has become increasingly important. This is an age of enlightenment in surgical pathology, and the authors of this new volume have captured this sense of excitement herein. This much praised and widely used reference manual has been extensively revised and expanded to cover the entire field of anatomic pathology. The Third Edition features the incorporation of full-color images in the text with updates of new diagnostic and prognostic information. New classifications and numerous new entities and histologic variants are fully explored. Useful immunostaining biomarkers and emerging molecular targets and relevant molecular findings that have emerged from recent genomic studies are incorporated in each chapter. Written by internationally recognized authorities, the comprehensive, evidence-based practice information is presented in an outline format that is clear and easy to follow. Up-to-date and richly detailed, Essentials of Anatomic Pathology, Third Edition offers both the pathologist-in-training and the practicing pathologist a concise summary of all the critical information needed to recognize, understand and interpret anatomic pathology.
Cytopathology -- Immunohistochemistry for the Surgical Pathologist -- Tumors of Unknown Primary -- Diagnostic Electron Microscopy -- Transplantation Pathology -- Microbiology for the Surgical Pathologist -- Forensic Pathology -- Autopsy -- Biomedical Infomatics for Anatomic Pathology -- Quality Assurance and Regulations for Anatomic Pathology -- Molecular Diagnostic Pathology -- Molecular Pathology of Solid Tumors -- Human Genetic Disorders -- Neuropathology -- Lymph Node -- Spleen -- Bone Marrow -- Neoplasms of the Skin and Immunodermatology -- Non-Neoplastic Skin Diseases -- Endocrine Pathology -- Bone and Joints -- Soft Tissue Tumors -- Tumors of the Salivary Glands -- Head and Neck -- Eye and Ocular Adnexae -- Mediastinum and Thymus -- Cardiovascular Pathology -- Lung and Pleura -- Breast -- Vulva and Vagina -- Uterus and Fallopian Tube -- Ovary and Peritoneum -- Placenta and Gestational Trophoblastic Disease -- Non-Neoplastic Renal Diseases -- Tumors of the Kidney -- Urinary Bladder -- Renal Pelvis, Ureter, and Urethra -- Prostate -- Testis and Testicular Adnexa -- Penis -- Esophagus and Stomach -- Small Intestine, Appendix, Colorectum, and Anus -- Pancreas -- Neoplastic Hepatobiliary Disease -- Neoplasms of the Liver and Biliary System.
Keywords: Medicine; Medical laboratories; Human anatomy; Pathology; Medicine & Public Health; Pathology; Anatomy; Laboratory Medicine